Musical journeys in Sumatra - Kartomi, Margaret J. (UPCC book collections on Project MUSE., 2012)
Although Sumatra is the sixth largest island in the world and home to an estimated 44 million Indonesians, its musical arts and cultures have not been the subject of a book-length study until now. Documenting and explaining the ethnographic, cultural, and historical contexts of Sumatra's performing arts, Musical Journeys in Sumatra also traces the changes in their style, content, and reception from the early 1970s onward._x000B__x000B_Having dedicated almost forty years of scholarship to exploring the rich and varied music of Sumatran provinces, Margaret Kartomi provides a fascinating ethnographic record of vanishing musical genres, traditions, and practices that have become deeply compromised by the pressures of urbanization, rural poverty, and government policy. This deeply informed collection showcases the complex diversity of Indonesian music and includes field observations from six different provinces: Aceh, North Sumatra, Riau, West Sumatra, South Sumatra, and Bangka-Belitung. Featuring photographs and original drawings from Kartomi's field observations of instruments and performances, Musical Journeys in Sumatra provides a comprehensive musical introduction to this neglected, very large island, with its hundreds of ethno-linguistic-musical groups.